Game Development Treasure Based Learning Discovery in Early Children in TK Az-Zikri Perbaungan District - Mifthahul Husna; Dewi Fitria (International Journal of Educational Research Excellence (IJERE), 2023)
This study aims to develop a treasure trove game based on discover learning to determine its feasibility and is ready to be used as a learning medium for early childhood at AZ ZIKRI Kindergarten, Perbaungan sub-district. This research is a type of research and development or research and development (R&D). This study uses the ADDIE model which focuses on developing discover learning-based treasure games which are equipped with a media use guidebook to make it easier for teachers to make and use discover learning-based treasure games. The instrument used to collect data is using a questionnaire on the validator based on the validation results of material experts getting a score of 90% and media experts of 83%. And interview instruments given by the teacher before and after getting a score of 93%. So it can be said that the development of a treasure game based on discovery learning in early childhood is very appropriate to be used as a learning medium in the Perbaungan sub-district.